Pengaruh Stock Split Terhadap Respon Investor - Yani Dwi Restanti; Herry Setyno (POLITEKNIK CAHAYA SURYA, 2021)
This study aims to determine the response of investors before and after the stock split, to determine the differences in stock returns and stock trading volume before and after the company does stocksplit. The companies used in this research sample are from the manufacturing, mining, financial and agricultural sectors. The research method used is an expalanatory research method with a quantitative approach, with the data analysis technique of one sample t-test and paired sample t-test. The results of the study inform that: (a) on the eighth day there is investor response after the company does stocksplit. Investors respond negatively as evidenced by negative abnormal returns. (b) there is no significant difference between stock returns before and after stocksplit. (c) there is a significant difference between TVA before and after stocksplit. Keywords: Stock split, abnormal return, return saham, TVA